Stabilising solutions to a class of nonlinear optimal state tracking problems using radial basis function networks - Ahmida, Zahir; Charef, Abdelfettah; Becerra, Victor M. (Zielona Góra: Uniwersytet Zielonogórski)
A controller architecture for nonlinear systems described by Gaussian RBF neural networks is proposed. The controller is a stabilising solution to a class of nonlinear optimal state tracking problems and consists of a combination of a state feedback stabilising regulator and a feedforward neuro-controller.
Keywords: nonlinear systems; optimal control; radial basis functions; neural networks; predictive control; feedforward control